Enabling Indonesian Pre-Service Teachers to Design Biology Learning Tools Using Metacognitive Strategy (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Pre-service biology teachers are required to be able to design innovative learning tools, which include lesson plans, student worksheets, and assessment. Metacognitive strategy, along with the assistance of Self Understanding Evaluation Sheet (SUES), could be considered to help them construct the learning tools. This study intended to train pre-service biology teachers’ skills in designing biology learning tools. It employed a one-shot case study design with 36 biology pre-service teachers at Universitas Negeri Surabaya, Indonesia, involved as participants. The implementation of the metacognitive strategy included revealing pre-service teachers’ prior knowledge, determining confidence, writing new knowledge, contrasting the prior knowledge with the new knowledge, and evaluating their understanding using the SUES. Results showed that all pre-service teachers were skillful in designing biology learning tools, of which the scores given by the lecturer and themselves showed the insignificant difference. Another finding portrayed that the pre-service teachers provided positive feedbacks as a response to the implementation of metacognitive strategy during the learning process in designing biology learning tools.